Própolis e cera vegetal na conservação de abacate Hass - Daiuto, Érica Regina [UNESP]; Minarelli, Philipp Herbst [UNESP]; Vieites, Rogerio Lopes [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
The aim of this work was to evaluate the quality of Hass avocado submitted to application of propolis and vegetable wax. The selected fruits were submitted to the treatments (1) without wax and without propolis, (2) with vegetable wax, (3) propolis alcoholic extract 100%, (4) wax and etanol 70%, (5) propolis alcoholic extract 2% and wax, (6) propolis alcoholic extract 4% and wax, (7) propolis alcoholic extract 6% and wax, (8) propolis alcoholic extract 8% and wax, and (9) propolis alcoholic extract 10% and wax. The fruits were maintained under refrigeration (10 +/- 1 degrees C and 90 +/- 5% relative humidity), being appraised every three days for 15 days and more 3 days of commercialization simulation at room temperature (23 +/- 1 degrees C and 18% relative humidity). The evaluation parameters were the weight loss, respiratory activity, pH, firmness, tritable acidity (AT), soluble solids (SS), and ratio. The results of weigth loss, respiratory activity and firmness were the most significant to show the difference among the treatments. 'Hass' avocado fruits submitted the application of propolis associated the vegetable wax present smaller weight loss, CO2 production and firmness in relation to the control fruits. The fruits of the treatment with propolis alcoholic extract 2% and wax presented the most promising results.
Propolis and vegetable wax in the conservation of Hass avocado
Keywords: Persea americana Mill.; refrigeration; modified atmosphere; firmness; postharvest